The Strength of Sibling Ties: Sibling Influence on Status Attainment in a Chinese Family - ZHANG, Qian Forrest (Institutional Knowledge at Singapore Management University, 2014)
What allowed eight siblings from a politically disadvantaged rural family to overcome institutional barriers and achieve upward mobility during Maoist China? What then restricted their children’s chances of upward mobility during the Reform era, when both family background and institutional environment were more favourable? In studying this anomalous case, whose experiences contradicted the well-documented effects of state policies and yet cannot be explained by parental influence, this study examines how adult siblings influenced each other’s status attainment processes, an issue largely neglected in the literature. Through comparing the micro-level mobility processes of the two generations in this family, I propose that, in times of rapid social change, sibling influence is more effective in generating status gain than parental influence, because the extensivity of sibling ties allows people to mobilize more relevant and heterogeneous social resources to facilitate social mobility.